Severe immune thrombocytopenia in pregnancy: a case report - Wakode, Shamrao Ramji; Sharma, Sakshi Pramod (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pregnancy when complicated with severe immune thrombocytopenia is a challenge both during labour and peripartum period. It’s management requires a multidisciplinary care approach. Severity of ITP may have adverse consequences on both maternal and fetal outcome. Present case report is of a patient with findings of chronic thrombocytopenia who came to antenatal outpatient department at 28 years of age with 7 months of amenorrhea with history of bleeding gums and purpura. She was monitored throughout third trimester of pregnancy. Ultrasonography findings showed severe oligohydramnios at 38 weeks and based on obstetric indications, elective cesarean section was planned after consultation with anesthetist and hematologist. Patient landed in intraoperative postpartum hemorrhage and was managed with medical management along with glove balloon tamponade. Patient was discharged on day 10 day along with her newborn. It shows that close monitoring of the clinical course and multidisciplinary care is critical to reach the correct treatment implication as well as potential management of such cases.